The effects of creatine supplementation on thermoregulation and isokinetic muscular performance following acute (3-day) supplementation - Rosene, J. M.; Matthews, T. D.; Mcbride, K. J.; Galla, A.; Haun, M.; Mcdonald, K.; Gagne, N.; Lea, J.; Kasen, J.; Farias, C. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The purpose of this investigation was to determine the effects of 3 d of creatine supplementation on thermoregulation and isokinetic muscular performance.